Automatic blood detection in capsule endoscopy video - Novozámský, Adam; Flusser, Jan; Tachecí, Ilja; Sulík, Lukáš; Bureš, Jan; Krejcar, Ondrej (Journal of biomedical optics, 2016)
We propose two automatic methods for detecting bleeding in wireless capsule endoscopy videos of the small intestine. The first one uses solely the color information, whereas the second one incorporates the assumptions about the blood spot shape and size. The original idea is namely the definition of a new color space that provides good separability of blood pixels and intestinal wall. Both methods can be applied either individually or their results can be fused together for the final decision. We evaluate their individual performance and various fusion rules on real data, manually annotated by an endoscopist.
Keywords: algoritmy; Intestine, Small; kapslová endoskopie; interpretace obrazu počítačem; Humans; lidé; gastrointestinální krvácení; Gastrointestinal Hemorrhage; Blood; Capsule Endoscopy; Image Interpretation, Computer-Assisted; tenké střevo; krev; Algorithms